Pengembangan Media Pembelajaran Berbasis Web Google Sites Pada Materi Reaksi Redoks Terintegrasi Nilai Islam - Selly Fah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was instigated with the aim of education that is to form students who are devout, knowledgeable, independent, and who have religious morals. Apart from that, there is a lack of learning media use utilizing digital technology so that learning is less varied. This research aimed at developing Web Google Sites based learning media focusing on Islamic Values Integrated Redox Reactions lesson and linking two sciences into one complete unit. DDR (Design and Development Research) model was used in this research. Feasibility test was done by distributing validation sheet to media experts, material experts, and integration experts, conducting practicality test by Chemistry subject teachers, and distributing student response questionnaire. The result of Web Google Sites based learning media was stated feasible, if it was valid and practical, a) the validity percentages obtained were 92.5% (very valid) by media expert validators, 90% (very valid) by material expert validators, and 90.6% (very valid) by integration expert validators; b) practicality percentage of Chemistry subject teacher assessment through practicality test was 100% (very practical); and c) the percentage of student response to the media was 87.33% with very good criteria. Based on these results, it could be identified that Islamic Values integrated Web Google Sites based learning media on Redox Reactions lesson was valid and practical, so it could be used in the learning.